A study of RNA m6A demethylases in oral epithelial dysplasia and oral squamous cell carcinoma - Chatchaphan Udompatanakorn; Pichamon Sriviriyakul; Patrayu Taebunpakul (Elsevier, 2023)
Purpose: N6-Methyladenosine (m6A) modification is involved in the tumorigenesis of various cancers. However, the roles of RNA m6A demethylases, fat mass and obesity-associated protein (FTO), and AlkB homolog 5 (ALKBH5) in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC) remain unclear. This study focuses on FTO and ALKBH5 expression by using immunohistochemistry. Material and methods: Twenty specimens each of OED, OSCC, and normal oral mucosa (NOM) were included. The expression pattern, the number of positive cells, the cell-staining intensity, and the histochemical scoring (H-score) were examined and analyzed. Results: In all the OED and OSCC specimens, FTO and ALKBH5 were mainly expressed with moderate to strong staining intensity in the nuclei of the abnormal epithelial cells, respectively. Regarding the NOM, both RNA demethylases showed mild cell staining intensity and was present in 50-60% of the specimens. Interestingly, the percentage of cell positivity, the cell-staining intensity, and the H-score of the FTO and ALKBH5 in NOM, OED, and OSCC were increased, respectively (p < 0.001). There was also a positive correlation between the FTO and ALKBH5 expressions in OSCC (r = 0.62, p = 0.003), but not in the NOM and OED. Conclusion: These results suggest a possible prognostic role of FTO and ALKBH5 expression in the malignant transformation of OED and tumor progression. Further studies are needed to elucidate the mechanisms underlying the roles of FTO and ALKBH5 in carcinogenesis.